A SYSTEMATIC APPROACH TO COST MANAGEMENT ENTERPRISES - Shulha, O. V.; Toporkova, Ye. O. (Science and Transport Progress, 2006)
The article is devoted to the issue of operational cost management which consists in the search and achievement of the optimum level both for the enterprise as a whole and for its structural subdivisions. Studies of the issue of operational cost management must have a systematic character. The article proposes a mechanism of cost management which consists of combination of organizational and economic elements.